1965
DOI: 10.1063/1.1703271
|View full text |Cite
|
Sign up to set email alerts
|

Infrared-Band Intensities of Adsorbed Carbon Monoxide

Abstract: It has been possible in favorable cases to measure the intensities of the infrared bands of CO adsorbed on different ZnO an? .supp.orted Cu, CuO, and Pt catalyst surfaces. For weak, reversible adsorption at room te~perat?-re, gtvmg nse to the bands in the frequency region 2132-2212 em-I, a unique correlation between mtenslty and frequency was found which apparently holds for a number of chemically different substrates. Values for both gaseous and dissolved CO fit the correlation reasonably well. A tentative ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

1980
1980
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(24 citation statements)
references
References 15 publications
0
21
0
3
Order By: Relevance
“…Seanor and Armberg [8] recorded frequencies appreciably higher than 2110 cm' with silica-supported copper. They observed a frequency of 2143 cm~, which gradually decreased to 2130 cm~at an increasing number of reduction and degassing treatments at 400 C. With Cu/Si02 and Cu/Al2 03 Pritchard et al also found a decrease in frequency from (2122 ±2) cm~to (2105 ±3) cm~,when the reduction temperature was raised from 140°C to 350°C.Admission of oxygen led to higher frequencies, which decreased again after reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seanor and Armberg [8] recorded frequencies appreciably higher than 2110 cm' with silica-supported copper. They observed a frequency of 2143 cm~, which gradually decreased to 2130 cm~at an increasing number of reduction and degassing treatments at 400 C. With Cu/Si02 and Cu/Al2 03 Pritchard et al also found a decrease in frequency from (2122 ±2) cm~to (2105 ±3) cm~,when the reduction temperature was raised from 140°C to 350°C.Admission of oxygen led to higher frequencies, which decreased again after reduction.…”
Section: Discussionmentioning
confidence: 99%
“…therefore attributed bands at higher frequencies than about 2110 cm' to the presence of not completely reduced copper. CO adsorbed on CuO shows frequencies of about 2135 cm~ [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…This result for CO is much different from those reported so far. [35][36][37][38][39] In the pioneering work by Seanor and Amberg, it is reported that E of the adsorbed CO species first decreases with increasing v(C0) frequency, then is almost constant and could even vanish in the 2150-2190 cm-' range, and then slightly increases in the 2190-2230 cm-' range.35 This feahue has been supported by subsequent experimental work^.^^-^* A qualitative explanation has been given by Brown and Doren~bourg.~~ They have also predicted that the v ( C 0 ) band would not be seen around 2175 cm-' because E could be almost 0 around this frequency. However, as pointed out by Sauer et al, these results probably have to be considered with care?O There is the case that relatively strong interactions, characterized by the large values of v ( C 0 ) (e.g.…”
Section: Comparison Between Adsorbed Species On Basmentioning
confidence: 97%
“…The binding of CO to surfaces of silica, silicates, metal oxides, and transition metals to form an adsorbed phase is well documented (13)(14)(15)(16)(17)(18)(19). In fact, C 0 is one of the most strongly chemisorbed of the simple gases.…”
Section: Reagent Solution and Reaction With Comentioning
confidence: 99%